Patterns, predictors and outcomes of asthma control and exacerbations during pregnancy: a prospective cohort study. Issue 1 (18th February 2016) - Grzeskowiak, Luke E.; Smith, Brian; Roy, Anil; Dekker, Gustaaf A.; Clifton, Vicki L.
There exists a paucity of data for socially disadvantaged populations describing patterns and predictors of asthma control status and exacerbations during pregnancy, and their relationship to adverse perinatal outcomes. Asthmatic women (n=189) were followed prospectively during pregnancy, with visits at 12, 20, 28 and 36 weeks gestation. Data on loss of control, recurrent uncontrolled asthma and moderate/severe exacerbations were collected at each visit and their relationship to perinatal outcomes examined following stratification for fetal sex. 50% of asthmatic women experienced a loss of control or moderate/severe exacerbation during pregnancy, with 22% of women experiencing a moderate/severe exacerbation. Factors associated with an increased risk of women experiencing recurrent uncontrolled asthma during pregnancy included smoking (relative risk 2.92, 95% CI 1.53–5.58), inhaled corticosteroid use at the beginning of pregnancy (relative risk 2.40, 95% CI 1.25–4.60) and increasing maternal age (relative risk 1.06, 95% CI 1.01–1.11). No factors were associated with moderate/severe exacerbations. Asthma control rather than exacerbations during pregnancy appeared to be most strongly correlated with perinatal outcomes. Following stratification by fetal sex, the presence of recurrent uncontrolled asthma was associated with an increased risk of being small for gestational age in women pregnant with females (33.3% versus 9.5%; p=0.018). In contrast, there was a nonsignificant increased risk of preterm birth in women with recurrent uncontrolled asthma that were pregnant with males (25.0% versus 11.8%; p=0.201) These results suggest that the key to improving perinatal outcomes lies in improving asthma control as early as possible in pregnancy and monitoring throughout pregnancy, rather than focusing on preventing exacerbations alone. Recurrent uncontrolled asthma during gestation is a greater contributor to poor perinatal outcomes than exacerbations http://ow.ly/X0OSa